Climate justice in India - Kashwan, Prakash (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Climate Justice in India brings together a collective of academics, activists, and artists to paint a collage of action-oriented visions for a climate just India. This unique and agenda setting volume informs researchers and readers interested in topics of just transition, energy democracy, intersectionality of access to drinking water, agroecology and women's land rights, national and state climate plans, urban policy, caste justice, and environmental and climate social movements in India. It synthesizes the historical, social, economic, and political roots of climate vulnerability in India and articulates a research and policy agenda for collective democratic deliberations and action. This crossover volume will be of interest to academics, researchers, social activists, policymakers, politicians, and a general reader looking for a comprehensive introduction to the unprecedented challenge of building a praxis of justice in a climate-changed world. This title is also available as Open Access on Cambridge Core.
Introduction : climate justice in India / Prakash Kashwan -- Urban climate justice in India / Eric Chu and Kavya Michael -- How just and democratic is India's solar energy transition? : an analysis of state solar policies in India / Karnamadakala Rahul Sharma and Parth Bhatia -- Extractive regimes in the coal heartlands of India : difficult questions for a just energy transition / Vasudha Chhotray -- Climate justice implications of the relationship between economic inequality and carbon emissions in India / Haimanti Bhattacharya -- Climate action plans and justice in India / Arpitha Kodiveri and Rishiraj Sen -- Social mobilizations for climate action and climate justice in India / Prakash Kashwan -- Reimagining climate justice as caste justice / Srilata Sircar -- Intersectional water justice in India : at the confluence of gender, caste, and climate change / Vaishnavi Behl and Prakash Kashwan -- Realizing climate justice through agroecology and women's collective land rights / Ashlesha Khadse and Kavita Srinivasan -- Conclusion : pathways to policies and praxis of climate justice in India / Prakash Kashwan and Eric Chu.
Title from publisher's bibliographic system (viewed on 03 Nov 2022).
Keywords: Climatic changes -- Government policy -- India; Climatic changes -- Social aspects -- Inida; Environmental justice -- India